Apnea-like suppression of respiratory motion: First evaluation in radiotherapy. Issue 2 (February 2016) - Péguret, Nicolas; Ozsahin, Mahmut; Zeverino, Michele; Belmondo, Bastien; Durham, André-Dante; Lovis, Alban; Simons, Julien; Long, Olivier; Duclos, Fréderic; Prior, John; Denys, Alban; Beigelman, Catherine; et al.
Abstract: Background and purpose: Compensation for respiratory motion is needed while administering radiotherapy (RT) to tumors that are moving with respiration to reduce the amount of irradiated normal tissues and potentially decrease radiation-induced collateral damages. The purpose of this study was to test a new ventilation system designed to induce apnea-like suppression of respiratory motion and allow long enough breath hold durations to deliver complex RT. Material and methods: The High Frequency Percussive Ventilation system was initially tested in a series of 10 volunteers and found to be well tolerated, allowing a median breath hold duration of 11.6 min (range 3.9–16.5 min). An evaluation of this system was subsequently performed in 4 patients eligible for adjuvant breast 3D conformal RT, for lung stereotactic body RT (SBRT), lung volumetric modulated arc therapy (VMAT), and VMAT for palliative pleural metastases. Results: When compared to free breathing (FB) and maximal inspiration (MI) gating, this Percussion Assisted RT (PART) offered favorable dose distribution profiles in 3 out of the 4 patients tested. PART was applied in these 3 patients with good tolerance, without breaks during the "beam on time period" throughout the overall courses of RT. The mean duration of the apnea-like breath hold that was necessary for delivering all the RT fractions was 7.61 min (SD = 2.3). Conclusions: This first clinical implementation of PART was found to be feasible, tolerable and offers new opportunities in the field of RT for suppressing respiratory motion.